Transformation of Selenium Nanoparticles by Lactobacillus acidophilus and Biological Activities of Selenium Nanoparticles Produced - Cimei CAI; Bingcheng LI; Zaijing SHENG; Yulin CHEN; Xueling LI; Bin HU; Jianfeng ZHU; Meiyan YANG; Wenfeng HU (Shipin gongye ke-ji, 2024)
Lactic acid bacteria have the ability to reduce sodium selenite to selenium nanoparticles (SeNPs). To obtain SeNPs in a more environmentally friendly way, this study first explored the effects of selenium concentration in the medium, selenium addition time and cultivating duration on the synthesis of SeNPs by Lactobacillus acidophilus, followed by a study of the particle size, zeta potential and antibacterial activity of the SeNPs produced. The results showed that when the selenium content in the medium was 0~600 μg/mL, the higher the selenium concentration was, the more nano-selenium was obtained. When the selenium concentration in the medium was higher than 600 μg/mL, the content of SeNPs in the fermentation broth decreased. The addition of sodium selenite in the early logarithmic stage of bacterial growth was more conducive to the synthesis of SeNPs. After 32 h of culture, SeNPs were almost no longer synthesized. The analysis using scanning electron microscopy and particle size and zeta potential analyzer revealed that the SeNPs produced by L.acidophilus were spherical in shape. Ultrasound treatment contributed to their release. The SeNPs carried a negative charge, with an absolute potential value of 40~50 mV, and their particle size predominantly ranged from 170~210 nm, exhibiting good stability. The results of antibacterial experiments showed that the SeNPs produced by L.acidophilus had inhibitory effects on the growth of Escherichia coli, Salmonella, Staphylococcus aureus and Bacillus subtilis. In conclusion, L.acidophilus can transform sodium selenite into SeNPs, which have good antibacterial activity.